$10 million from SAMHSA for pregnant women, family, children. Issue 8 (18th February 2022) - Knopf, Alison
Abstract : The Substance Abuse and Mental Health Services Administration (SAMHSA) on Feb. 3 announced that it is accepting applications for a $10 million grant program to provide women and their children with substance use treatment and recovery support services across residential and outpatient settings. Applications are due April 4.